Verulamium Excavations. Volume II - Shephard, Frere (Reports of the Research Committee of the Society of Antiquaries of London, 1983)
This is the second volume on the excavations at St Alban's (Verulamium), Hertfordshire, in southern England, undertaken between 1955 and 1961, which covers all the work of those years (other than the row of shops in Insula XIV, described in volume 1). The Belgic mint, the Roman defences, the forum, the northern monumental arch, and the various intra-, and extra-mural structures are discussed, and there is a full treatment of the dating evidence, especially pottery, and a revised assessment of the town's layout, history and status in Roman Britain.